2003
DOI: 10.1128/aac.47.1.204-210.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Clonal Lineage of VanA-Type Enterococcus faecalis Predominates in Vancomycin-Resistant Enterococci Isolated in New Zealand

Abstract: Avoparcin was used as a feed additive in New Zealand broiler production from 1977 until June 2000. We report here on the effects of the usage and discontinuation of avoparcin on the prevalence of vancomycinresistant enterococci (VRE) in broilers. Eighty-two VRE isolates were recovered from poultry fecal samples between 2000 and mid-2001. VRE isolates were only obtained from broiler farms that were using, or had previously used, avoparcin as a dietary supplement. Of these VRE isolates, 73 (89%) were VanA-type E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 48 publications
3
70
1
3
Order By: Relevance
“…However, community carriage linked to a consumption of imported and contaminated food cannot be excluded. Studies performed in New Zealand described a www.intechopen.com supposed dissemination of vanA-type resistance among E. faecalis strains rather then E. faecium in a background of generally low level of vancomycin resistance (Manson et al, 2003a;Manson et al, 2003b). VRE epidemiology in other Australasian countries reflects a similar scenario as in Europe or Northern America with vanA-type resistance highly prevalent among E. faecium.…”
Section: Asia Australia and New Zealandmentioning
confidence: 87%
See 2 more Smart Citations
“…However, community carriage linked to a consumption of imported and contaminated food cannot be excluded. Studies performed in New Zealand described a www.intechopen.com supposed dissemination of vanA-type resistance among E. faecalis strains rather then E. faecium in a background of generally low level of vancomycin resistance (Manson et al, 2003a;Manson et al, 2003b). VRE epidemiology in other Australasian countries reflects a similar scenario as in Europe or Northern America with vanA-type resistance highly prevalent among E. faecium.…”
Section: Asia Australia and New Zealandmentioning
confidence: 87%
“…Exchange of resistant strains among different ecosystems is less probable due to the supposed ecovar association, especially among hospital-associated E. faecium strains (see chapter 5), although dissemination across host barriers of vancomycin-and multi-resistant enterococci was described anecdotally, especially for the less strongly host-adapted E. faecalis strains (Manson et al, 2003a;Manson et al, 2003b;Manson et al, 2004;Agerso et al, 2008;Larsen et al, 2010;Hammerum et al, 2010;Freitas et al, 2011a). Vancomycin resistance among enterococci most probably spreads via a dissemination of mobile genetic elements of variants of the vanA-type element Tn1546 mostly located on mobilizable or conjugative plasmids (Sletvold et al, 2007;Novais et al, 2008;Sletvold et al, 2008;Freitas et al, 2009;Rosvoll et al, 2009;Sletvold et al, 2010;Laverde Gomez et al, 2011;Werner et al, 2011b;Freitas et al, 2011b).…”
Section: Localization and Spread Of Vana-and Vanb-type Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Restriction or DNA-modifying enzymes and other molecular biology reagents were obtained from Roche Diagnostics or New England Biolabs. Genomic DNA of E. faecalis was isolated as previously described (30). Transformation of E. faecalis cells grown in the presence of glycine was performed as described by Shepard and Gilmore (29).…”
Section: Methodsmentioning
confidence: 99%
“…VRE have been isolated from poultry sources in New Zealand (18); however, VRE causing infection in the clinical situation are rare (17). Chromosomal macrorestriction analysis of VRE isolates from poultry and humans in New Zealand has demonstrated that a dominant clonal lineage of vancomycin-resistant Enterococcus faecalis (VREF) exists (18). In this report, we describe the first VREF isolate (AR01/DG) recovered from a dog in New Zealand and show that it belongs to the same clonal lineage described in poultry and humans.…”
mentioning
confidence: 99%